La notion de protection du public dans la réforme du droit professionnel québécois : une analyse socio-politique - Belley, Jean-Guy (Les Cahiers de droit, 1980)
This paper analyses the reform of the law governing professional occupations in Quebec from a socio-political standpoint. By focusing on the ideological level, the reform is seen as the result of the interaction of five competing ideologies : corporatism traditionnally dominant in the professional laws, technocratism that asserted itself in the context of the Revolution tranquille and gave its first impulse to the reform, neoclassic liberalism as expressed in the works of the Chicago School economists, communitarian ideology inspiring the practices of community-centered services among popular groups and consumerism advocating the interests of middle and upper class consumers. In conclusion, it appears that the Code des professions enacted in 1973 proceeded from a compromise between corporatism and technocratism which turned largely to the advantage of the former. But the next step could be quite different. As a matter of fact, the recent positions expressed by the Office des professions du Québec reveal a clear tendency to rely upon consumerism and more fundamentally upon liberalism to carry on the reform. If so, the private law perspective based on a new contract of professional service would become more determinative than articulated public policies in the future regulation of the professional services industry. Bu obtaining a significant reduction of traditional corporatist powers — particularly the price-fixing one — while preventing a more pronounced public intervention, liberal forces would be the ultimate beneficiaries of the reform.